The Influence of Play Activities, Nutritional Status and Motor Ability on The Physical Fitness of Primary School Students - Putra, Riwaldi; Putra, Deri; Nanda, Fitri Agung (JUMORA: Jurnal Moderasi Olahraga, 2024)
This research aims to reveal the influence of playing activities, nutritional status and motor skills on physical fitness. This research method is quantitative using a path analysis approach. The population of this study was all students at SD N 14 Jati Tanah Tinggi, Padang City, totaling 163 people. The sampling technique was carried out by purposive sampling, with a total sample of 49 people. Data was collected by filling out questionnaires for playing activities, measuring body weight and height for nutritional status, throwing a basketball, running for four seconds, passing a ball against a wall and jumping without a start to measure motor skills, and to measure students' physical fitness, the TKJI test was used to elementary school age children. The results of research and data analysis show that: (1) Playing activities have a direct and significant effect on physical fitness by 12.6% (2) Nutritional status has a direct and significant effect on physical fitness by 12.4% ( 3) Motor Ability has a direct and significant effect on physical fitness by 9.2% (4) Playing activities have an indirect effect on Physical Fitness through Motor Ability by 17.7% (5) Nutritional status has an indirect effect on Physical Fitness through Motor Ability is 28.1% (6) Playing Activities, Nutritional Status and Motor Ability simultaneously influence students' Physical Fitness by 48.2%